Netværksbaseret læring - Pilegaard, Morten (HERMES - Journal of Language and Communication in Business, 2003)
This paper discusses pedagogical and technological aspects of networked learning and the interplay between pedagogical principles, information technology and the educa-tional and organisational frameworks in the context of a distance-teaching course for Danish graduates seeking research-based further education and training in English for medical purposes. The empirical basis is an evaluation report of a second generation distance-teaching course where applied information technologies are geared to maxi-mum pedagogical efficiency by presenting on-line course materials in a flat visual de-sign and by facilitating dialogue between course participants working in teams.